PTH-039 The First Randomised Controlled Trial of Endocuff Vision® Assisted Colonoscopy Versus Standard Colonoscopy for Polyp Detection in Bowel Cancer Screening Patients (E-Cap Study). (17th August 2016) - Bhattacharyya, R; Chedgy, F; Kandiah, K; Fogg, C; Higgins, B; Gadeke, L; Thursby-Pelham, F; Ellis, R; Goggin, P; Longcroft-Wheaton, G; Bhandari, P
Abstract : Introduction: Up to 25% polyps are missed during colonoscopy. The Endocuff Vision® is a cap with soft flexible arms that attaches to the colonoscope tip and improves views during withdrawal. We have performed the first randomised controlled trial to identify the role of Endocuff Vision® in improving polyp detection. We aim to investigate the impact of Endocuff Vision® assisted colonoscopy on polyp detection, as compared to standard colonoscopy, in the UK Bowel Cancer Screening Programme (BCSP). Methods: Single centre, parallel group, randomised controlled trial. Ethics ref: 14/SC/0207. Adopted on UKCRN portfolio (ID: 16985). Patients attending for BCSP colonoscopy were stratified based on attendance for index screening colonoscopy or for polyp surveillance. Within each stratum participants were randomised to either Standard or Endocuff assisted colonoscopy. All procedures were performed by accredited BSCP endoscopists, who have carried out > 5000 colonoscopies and have caecal intubation rates of >90%. Results: 534 patients recruited from Sep 2014 to Sep 2015. 3 excluded due to new diagnosis of polyposis syndrome. 531 were included and randomised to the 2 study arms. No significant difference was seen between the 2 groups for the primary endpoint of number of polyps per patient. Secondary endpoints: No significant difference was observed between the 2 groups for adenoma detection rate (ADR) or number of adenomas per patient (Table 1 ). No significant adverse events were encountered during the study in either arm. The cecal intubation time was not prolonged and patients did not experience any additional discomfort due to the Endocuff Vision. Conclusion: In the UK, bowel cancer screening is performed by highly experienced endoscopists. Our results suggest that in expert hands, ADR exceeds 60% even without Endocuff. In such settings, Endocuff Vision did not improve polyp detection rates (PDR) or ADR. However, it did not cause any adverse events, prolong procedure duration or cause additional discomfort. These data demonstrate the safety and feasibility of Endocuff. However, no additional gain was demonstrated in expert hands. Disclosure of Interest: None Declared